2014
DOI: 10.1039/c3cc47675h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity and stability of organophosphorus hydrolase via interaction with an amphiphilic polymer

Abstract: A simple approach to enhancing the activity and stability of organophosphorous hydrolase (OPH) is developed based on interactions between the hydrophobic poly(propylene oxide) (PPO) block of amphiphillic Pluronics and the enzyme. This strategy provides an efficient route to new formulations for decontaminating organophosphate neurotoxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…To the best of our knowledge, the use of liquid polymers for dust control is rare; therefore, this concept was tested by evaluating the dust suppressive effectiveness of commercially available liquid polymers. 23,24 When selecting liquid polymers, we considered water solubility, liquid phase in ambient conditions, biocompatibility, and environmentally friendliness in order to readily apply this technology to current watering practices. These preconditions resulted in the selection of liquid amphiphilic poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) (PEO-PPO-PEO) triblock copolymer and liquid hydrophilic polyethylene glycol (PEG), used in food, cosmetics, and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the use of liquid polymers for dust control is rare; therefore, this concept was tested by evaluating the dust suppressive effectiveness of commercially available liquid polymers. 23,24 When selecting liquid polymers, we considered water solubility, liquid phase in ambient conditions, biocompatibility, and environmentally friendliness in order to readily apply this technology to current watering practices. These preconditions resulted in the selection of liquid amphiphilic poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) (PEO-PPO-PEO) triblock copolymer and liquid hydrophilic polyethylene glycol (PEG), used in food, cosmetics, and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Protein‐based materials have grown increasingly valuable due to their diverse functionality, substrate specificity, and high catalytic activity as new routes toward biofuel synthesis, drug delivery, polymer synthesis, neurotoxin detection, and remediation, and industrial reactions . Materials for these applications must have good mechanical properties, retain or improve the function and stability of the protein, allow for transport of reactants and products through the material, and control the orientation and nanoscale arrangement of proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches to enhance enzyme stability and activity for decontaminating OP neurotoxins are based on interactions between the hydrophobic polypropylene oxide (PPO) block of amphiphilic Pluronics and enzymes such as PTE. Although a detailed mechanism of how the PPO block may enhance the catalytic activity of OP-degrading enzymes has not yet been elucidated, it has been demonstrated that the aggregate has also increased resistance to inhibition by methanol, enhanced thermal stability, an extended shelf life, as well as an expanded substrate range [174]. Hydrogelforming PTE variants have also been generated by genetically fusing this enzyme to alpha-helical leucine zipper domains (H), unstructured soluble linker domains (S) and polyhistidine purification tags, resulting in the formation of hydrogels, which proved to be effective catalytic biomaterials [175].…”
Section: Enzyme Immobilization and Biotechnological Applicationsmentioning
confidence: 99%